PENINGKATAN HASIL BELAJAR GEOGRAFI KOMPETENSI ATMOSFER DAN DAMPAKNYA BAGI KEHIDUPAN MELALUI PEMBELAJARAN MODEL FIRING LINE - Sovia Isniati (Ideguru: Jurnal Karya Ilmiah Guru, 2017)
Firing Line application Research model implemented in SMA Negeri 1 KRETEK aims to improve the learning achievement of students in geography subjects of X4 class. This was a classroom action research (PTK) with research subjects involving the X4 class . The research was conducted in The research used the Kemmis and Taggart’s model. Each cycle consisted of four stages, namely: planning, acting, observation, and reflection. The document were collected through observations, interviews and document reviews, and descriptive quantitative analysis. This research was conducted for two rounds (cycles) and improvements was carried out in learning strategies of individual cycle. Results of observation and tests served as reflection material for the next action plan. Results showed improvement that student achieved through the application of Firing Line model consisting of increase of scores and test scores; students’ test score average in the first cycle was 62.5, then in the second cycle it increased to be 75,57 and the completeness percentage increased from 47,62% into 86.67%. The conclution of this researc is Application of Firing Line Learning Model can to Increase the learning achievement in Geography Subject competence atmosphere and ist impact for life at the X4 Class at SMA N I Kretek